PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA MELALUI PROSES DIVERSI PADA BAPAS KELAS I PADANG - Lily Reni (UNES Journal of Swara Justisia, 2019)
Based on the General provisions on article 1 point (4) of the Act No. 12 Year 1995Incerning Corrections Correctional Hall explains that the institution is hereinafterreferred to as BAPAS to carry out Correctional Clients guidance. Law number 11 Year2012 about the criminal justice system of the child in article 1 point (7) explains that theDiversion was the transfer of case settlement children from criminal justice processes toprocesses outside of criminal justice. In terms of legal protection and that the rights of thechild not to be broken then legal aid in children by Bapas through Civic Mentors (PK)always accompany the child to provide reinforcement psychological againstperpetrators.Based on the above, the background can be formulated as the following issues: first, howis the legal protection given to the perpetrators of criminal acts in the process of diversionby Bapas Kelas I Desert?.Second, whether the constraints faced by the communitySupervisor Bapas Kelas I Pasture in the granting of legal protection against theperpetrators of the crime? and how the effort of overcoming these constraints?.Based onthe results of research and discussion, can be summed up as follows; First, besidesperlindungan law provided by Correctional Hall class of I Pastureagainst the perpetratorof the criminal offenceby the criminal justice system diversion Children withmentoring,doing research Viablein order for rights-the rights ofason not to be broken as well asattempting to do a versioned to provide strengthening psychologically against childabuserto face the process of law faced by child abusers. Second, constraints encountered inperforming the duties of Correctional Hall class I the field include rule of law related tothe regulation of the Minister Kemenkumham, inadequate coordination with lawenforcement related implementation legislation, SPPA the low quality of human resources,lack of facilities and infrastructure, family factors clients, and budget constraints. Effortsto address these constraints need to be issued Ministerial Regulation for the strengtheningof the position of the officer Supervising the community, maximize coordination with lawenforcement related legislation SPPA, requiring PK in socialization training or educationto improve the quality of HUMAN RESOURCES, complete infrastructure, dissemination toparents of clients, as well as the need to increase the budget.